Existence of Nonoscillatory Solutions to Second-Order Neutral Delay Dynamic Equations on Time Scales. (11th October 2009) - Li, Tongxing; Han, Zhenlai; Sun, Shurong; Yang, Dianwu
Abstract : We employ Kranoselskii's fixed point theorem to establish the existence of nonoscillatory solutions to the second-order neutral delay dynamic equation[ x ( t ) + p ( t ) x ( τ 0 ( t ) ) ] Δ Δ + q 1 ( t ) x ( τ 1 ( t ) ) − q 2 ( t ) x ( τ 2 ( t ) ) = e ( t ) on a time scale 𝕋 . To dwell upon the importance of our results, one interesting example is also included.